THE IMPACT OF MORPHOLOGICAL STUDY ON FOLKLORE LUTUNG KASARUNG TEXT FOR EFL LEARNERS - Anak Agung Putu Arsana; Ni Nyoman Saka Nimas Ajeng Leonita; Ida Ayu Praba Iswari Dewi; Ni Wayan Setiani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2022)
This study endeavored to portray and make sense of the morpheme in the folklore of Lutung Kasarung, the structural and functional classification of affixes and its impact on the analysis for EFL learners. This study was planned as a qualitative study. This study was led on the folklore of Lutung Kasarung. The data were gathered by perusing the text of Lutung Kasarung, then, underlying the words in the text which contain morpheme, base, stem, root and affixes, after that, it is revamped the information methodically. The impact of producing a morphological study on folklore text for EFL learners is, improving their vocabulary, developing their knowledge of word structure, enhance their communication and writing skill. The examination was concerned about: morpheme, analysis of base, stem and root, and affixes. In first table (1) the researcher found 54 words with free and bound morphemes. In the second (2) table there are 52 words that have suffixes, 2 words have prefixes, and 1 word has prefix and suffix. Last table (3) researchers found that are 49 words called base and 5 words have suffixes called stem and the last thing all of words that total 54 words have called root.